ANALISIS INFORMASI AKUNTANSI DIFERENSIAL DALAM PENGAMBILAN KEPUTUSAN PENGGANTIAN AKTIVA TETAP PADA UD. SINGKIL SERVICE MANADO - Salasa, Juliana Y.P; Nangoi, Grace B.; Rondonuwu, Sintje (Universitas Sam Ratulangi, 2018)
In the modern era, there are many innovations created by the company to expand the company's activities, with one of them using fixed like a good machine. But in a fixed condition, companies can see costs such as fees for taking results from the machine. The purpose of this research is to find out how information can be used. The analytical method used in this study is a qualitative descriptive method, where the method of this research is carried out in detail by collecting data from the company and analyzing the results of the analysis. The results of this study are UD. Singkil Service Manado can apply the concept of Differential Accounting Information in decision making. Freezing can be useful for costs that can harm the company. Companies should be able to replace the old machine with a new engine because there is a large enough differenceKeywords: Differential Accounting Information, Replacement of fixed assets